Synthesis, Experimental and Theoretical Study of Azidochromones - Nárvaez Ordóñez, Ena Gabriela (2022)
A series of 2-(haloalkyl)-3-azidomethyl and 6-azido chromones has been synthetized, characterized and studied by theoretical (DFT calculations) and spectroscopic methods (UV-Vis, NMR). The crystal structure of 3-azidomethyl-2-difluoromethyl chromone, determined by X-ray diffraction methods, shows a planar framework due to extended π-bond delocalization. Its molecular packing is stabilized by F∙∙∙H, N∙∙∙H and O∙∙∙H hydrogen bonds, π∙∙∙π stacking and C–O∙∙∙π intermolecular interactions. Moreover, AIM, NCI and Hirshfeld analysis evidenced that azido moiety has a significant role in the stabilization of crystal packing through weak intermolecular interactions, where analysis of electronic density suggested closed-shell (CS) interatomic interactions.